Health-related quality of life of a general population over 40 years old in Mazandaran province, Iran - Reza Ali Mohammadpour (Payesh, 2011)
Objective(s): To study health-related quality of life of a general population over 40 years old in Mazandaran province, Iran. Methods: This was a cross-sectional study. A sample of the general population aged 40 and over were studied. Quality of life was measured using the Iranian version of SF-36. Data were analyzed in a descriptive fashion. Results: In all data from 1183 individuals were analyzed. Of these, 46.87 %  rated their health as excellent or very good. There were significant differences in quality of life scores between males and females and among urban and rural populations. However, vitality score was higher in those who were living in rural areas. Conclusion: The finding suggest that there are inequalities in health status among different genders and urban and rural populations. The need for policies to reduce this seems necessary.